G.W.F. Hegel. - Siep, Ludwig (Klassiker auslegen., 2014)
The essays in this first-ever complete commentary on Hegel's philosophy of law combine interpretation of all important textual passages with a selection of different interpretative perspectives drawn from international Hegel research.